Are you sure? : learning about proof - French, Doug, ....-; Stripp, Charlie, ....- (Leicester : Mathematical Association, 2005)
Proof is vital to the activities of mathematicians. Proof has been neglected in the National Curriculum. This important book discusses issues related to learning about proof in the classroom. Aimed mainly at teachers in the last four years schooling Are You Sure? contains proofs and teaching ideas of varying difficulty.
Keywords: Wiskunde -- Secundair onderwijs